Mesenchymal stem cell-originated exosomal circDIDO1 suppresses hepatic stellate cell activation by miR-141-3p/PTEN/AKT pathway in human liver fibrosis - Li Ma; Junfeng Wei; Yanli Zeng; Junping Liu; Erhui Xiao; Yuehua Kang; Yi Kang (Taylor & Francis Group, 2022)
Liver fibrosis is a common pathologic stage of the development of liver failure. It has showed that exosomes loaded with therapeutic circRNAs can be manufactured in bulk by exosome secreted cells in vitro, thus enabling personalized treatment. This study aimed to investigate the role of exosome-based delivery of circDIDO1 in liver fibrosis. Levels of genes and proteins were examined by qRT-PCR and Western blot. Cell proliferation, apoptosis, and cell cycle were analyzed by using cell counting kit-8 (CCK-8) assay, EdU assay, and flow cytometry, respectively. The binding between circDIDO1 and miR-141-3p was confirmed by dual-luciferase reporter, RNA pull-down and RIP assays. Exosomes were isolated by ultracentrifugation, and qualified by transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA) and Western blot. CircDIDO1 overexpression or miR-141-3p inhibition suppressed the proliferation, reduced pro-fibrotic markers, and induced apoptosis as well as cell cycle arrest in hepatic stellate cells (HSCs) by blocking PTEN/AKT pathway. Mechanistically, circDIDO1 acted as an endogenous sponge for miR-141-3p, further rescue experiments showed that circDIDO1 suppressed HSC activation by targeting miR-141-3p. Extracellular circDIDO1 could be incorporated into exosomes isolated from mesenchymal stem cells (MSCs), and transmitted to HSCs to restrain HSC activation. Clinically, low levels of serum circDIDO1 in exosome were correlated with liver failure, and serum exosomal circDIDO1 had a well diagnostic value for liver fibrosis in liver failure patients. Transfer of circDIDO1 mediated by MSC-isolated exosomes suppressed HSC activation through the miR-141-3p/PTEN/AKT pathway, gaining a new insight into the prevention of liver fibrosis in liver failure patients.